Big data : techniques and technologies in geoinformatics - Karimi, Hassan A (Boca Raton, Fl. : CRC Press, 2014)
Big data has always been a major challenge in geoinformatics as geospatial data come in various types and formats, new geospatial data are acquired very fast, and geospatial databases are inherently very large. And while there have been advances in hardware and software for handling big data, they often fall short of handling geospatial big data efficiently and effectively. Big Data: Techniques and Technologies in Geoinformatics tackles these challenges head on, integrating coverage of techniques and technologies for storing, managing, and computing geospatial big data.
Includes bibliographical references and index.
Keywords: Geography -- Data processing; Big data; Geographic information systems; Geospatial data; High performance computing